Narrative Approaches to Teacher Agency: How Educators’ Stories Shape Educational Change - Erwin Erwin; Teboho Maseko; Syafiq Amir; Saiful Fallah (Yayasan Adra Karima Hubbi, 2025)
Background. Teacher agency plays a crucial role in educational transformation, yet its narrative dimensions remain underexplored. This study addresses how educators' stories shape their capacity to influence professional practices and institutional policies amid reform initiatives, drawing on narrative theory to examine storytelling as a sense-making tool for navigating complex educational landscapes. Purpose. The primary aim is to investigate how teachers construct and enact professional agency through narrative structures in relation to educational change, identifying patterns across career stages and reform types to understand temporal, collective, and contextual influences on agency development. Method. Data collection included three life history interviews per participant over six months, supplemented by artifacts and researcher reflections. Analysis utilized Clandinin and Connelly's three-dimensional framework, incorporating structural, thematic, and dialogic techniques with member checking for trustworthiness. Results. Findings revealed three dominant narrative plots: progressive (heroic transformation), tragic (constrained persistence), and comedic (pragmatic improvisation). Career stage variations showed early-career teachers focusing on individual agency, mid-career on collective action, and veterans on temporal depth. Conclusion., providing a framework for understanding how stories mediate reform implementation and empower educators. This approach highlights the potential for narrative practices to foster equitable, context-sensitive transformations in education.